2018
DOI: 10.1038/s41598-018-27682-w
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Hypertension Affects the Rat Gut Microbiome

Abstract: We have analysed whether pulmonary arterial hypertension (PAH) alters the rat faecal microbiota. Wistar rats were injected with the VEGF receptor antagonist SU5416 (20 mg/kg s.c.) and followed for 2 weeks kept in hypoxia (10% O2, PAH) or injected with vehicle and kept in normoxia (controls). Faecal samples were obtained and microbiome composition was determined by 16S rRNA gene sequencing and bioinformatic analysis. No effect of PAH on the global microbiome was found (α- or β-diversity). However, PAH-exposed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 61 publications
10
66
1
Order By: Relevance
“…In a rat model of PAH induced by a single dose of Sugen5416 plus chronic hypoxia for two weeks, we found two main hallmarks of gut dysbiosis: a three-fold increase in F/B ratio, driven by a decrease in all Bacteroidetes families in PAH animals (2-10-fold decrease) and no changes in Firmicutes abundance. Furthermore, feces from PAH rats present a decreased in acetate-producing bacteria, accompanied by a reduced serum acetate, without changes in butyrate and lactate producing bacteria [130]. In contrast, we did not find global differences in microbial diversity and richness, as happened in other diseases [124].…”
Section: Microbiotacontrasting
confidence: 71%
See 2 more Smart Citations
“…In a rat model of PAH induced by a single dose of Sugen5416 plus chronic hypoxia for two weeks, we found two main hallmarks of gut dysbiosis: a three-fold increase in F/B ratio, driven by a decrease in all Bacteroidetes families in PAH animals (2-10-fold decrease) and no changes in Firmicutes abundance. Furthermore, feces from PAH rats present a decreased in acetate-producing bacteria, accompanied by a reduced serum acetate, without changes in butyrate and lactate producing bacteria [130]. In contrast, we did not find global differences in microbial diversity and richness, as happened in other diseases [124].…”
Section: Microbiotacontrasting
confidence: 71%
“…However, it could be speculated that part of the effects of the dietary factors mentioned above in PAH might be due to changes in the microbiota. We demonstrated for the first time that there are several changes in the gut microbiota in PAH [130]. In a rat model of PAH induced by a single dose of Sugen5416 plus chronic hypoxia for two weeks, we found two main hallmarks of gut dysbiosis: a three-fold increase in F/B ratio, driven by a decrease in all Bacteroidetes families in PAH animals (2-10-fold decrease) and no changes in Firmicutes abundance.…”
Section: Microbiotamentioning
confidence: 71%
See 1 more Smart Citation
“…Several other studies have described the relationship between cardiovascular diseases and dysbiosis. 20,21,23,28 For example, Yang et al have demonstrated that F/B ratios are higher in two different animal models of systemic hypertension than in control rats. 28 They have also shown that patients with systemic hypertension have distinct gut microbiota compositions from those of healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 is shown to be associated with arterial stiffness in healthy individuals [117]. Interestingly, induced pulmonary arterial hypertension in rats also leads to a greater Firmicutes to Bacteroidetes ratio in the gut microbiota [118]. The gut dysbiosis might play a pathophysiological role in pulmonary arterial hypertension by altering the host immunologic, hormonal and metabolic homeostasis.…”
Section: Gut Microbiota and Arterial Remodellingmentioning
confidence: 99%